Integrated prognostic role of the glucose-to-potassium ratio and serum sodium levels in patients with HFPEF - Lysenko, V. A.; Лисенко, Владислав Андрійович (Запорізький державний медико-фармацевтичний університет, 2025)
Aim. To evaluate the prognostic significance of GPR and serum sodium in patients with HFpEF during a 12-month follow-up.
Keywords: тези доповідей